The role of immune regulation in HBV infection and hepatocellular carcinogenesis - Zheng, Hailong; Xu, Bingchen; Fan, Yiyu; Tuekprakhon, Aekkachai; Stamataki, Zania; Wang, Fei (Frontiers in Immunology, 2025)
Hepatitis B virus (HBV) infection is a well-documented independent risk factor for developing hepatocellular carcinoma (HCC). Consequently, extensive research has focused on elucidating the mechanisms by which HBV induces hepatocarcinogenesis. The majority of studies are dedicated to understanding how HBV DNA integration into the host genome, viral RNA expression, and the resulting protein transcripts affect cellular processes and promote the malignant transformation of hepatocytes. However, considering that most acute HBV infections are curable, immune suppression potentially contributes to the critical challenges in the treatment of chronic infections. Regulatory T cells (Tregs) are crucial in immune tolerance. Understanding the interplay of Tregs within the liver microenvironment following HBV infection could offer novel therapeutic approaches for treating HBV infections and preventing HBV-related HCC. Two viewpoints to targeting Tregs in the liver microenvironment include means of reducing their inhibitory function and decreasing Treg frequency. As these strategies may disrupt the immune balance and lead to autoimmune responses, careful and comprehensive profiling of the patient’s immunological status and genetic factors is required to successfully employ this promising therapeutic approach.